Testing the Causal Relationship between Economic Growth and Renewable Energy Consumption: Evidence from a Panel of EAGLE Countries - Salehin, Meshkatus; Kiss, Judit T. (International Journal of Energy Economics and Policy, 2022)
Economic growth and energy consumption are two main factors that play a vital role in any country’s overall development. The researchers built and described different econometric models to evaluate the relationship between the two variables. In this research, we chose 15 emerging economy countries to examine the relationship between renewable energy consumption and economic growth. We applied the panel ARDL approach with PMG estimator which one of the best approaches to model long-term and short-term dynamics. Gross domestic product per capita and renewable energy consumption as a percent of total final energy consumption has a positive and significant coefficient when used as an independent variable in the long run. We also checked causality between the variables to test how the causal relationship occurs. We also found a causal relation from economic growth to renewable energy consumption, thus proving the conservation hypothesis. However, our outcome showed that the relationship is not statistically significant between renewable energy and economic growth in the short run. Finally, we pointed out few policy recommendations and future work directions based on our works at the end of this article.